Opportunities for wastewater heat recovery in Hungary and its role in the circular economy - Gabnai, Zoltán; Németh, Kornél; Péter, Erzsébet; Sertolli, Ardit; Pestisha, Albiona; Mezőfi, Nóra; Bai, Attila (Applied Studies in Agribusiness and Commerce, 2021)
Most of the energy content of wastewater can be found in wastewater heat, however, its recovery is limited. In this article, the current situation, future opportunities of wastewater heat recovery are presented based on secondary data collection, mentioning the constraints and main influencing factors of sustainable implementation of heat recovery systems in Hungary. Besides, the already existing systems are described. As regards the capacities of treatment plants, 103 of the 574 domestic plants have a capacity of over 20,000 Population Equivalent (PE), of which 25 plants have a capacity of over 100,000 PE. According to our calculations, in big cities/capitals (20.000 – 100.000, and over 100.000 inhabitants), it may be possible to recover wastewater heat sustainably in several places. In small towns (5.000 – 20.000 inhabitants), wastewater heat recovery can be technologically and economically sustainable only in the presence of agricultural or industrial plants with high and continuous wastewater feed into the pipeline system. Taking into account the temperature conditions at each place of use and their estimated fluctuations, it can be said that proper, careful planning, sizing and implementation have a crucial effect on the efficiency of microbiological activity in the treatment plants. In bigger cities, of course, the effect of the temperature drop of one main collector may be minimal, however, in smaller and medium-sized settlements, excessive heat extraction may result in complete inhibition or cessation of nitrification. In Hungarian case studies, the maximum acceptable temperature drop is approx. 2-3 °C. It can be stated that energy recovery from wastewater may be very promising considering the size and temperature limitations. Therefore, the rational recovery of wastewater heat can be an important part of the implementation of circular economy and sustainable energy utilization in wastewater management, resulting in significant energy savings and pollutant reduction. JEL CODE: Q25